2013
DOI: 10.1098/rstb.2013.0021
|View full text |Cite|
|
Sign up to set email alerts
|

The mystery of extreme non-coding conservation

Abstract: Regions of several dozen to several hundred base pairs of extreme conservation have been found in non-coding regions in all metazoan genomes. The distribution of these elements within and across genomes has suggested that many have roles as transcriptional regulatory elements in multi-cellular organization, differentiation and development. Currently, there is no known mechanism or function that would account for this level of conservation at the observed evolutionary distances. Previous studies have found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 118 publications
4
82
0
Order By: Relevance
“…An equivalent region driving the expression to the developing eye is present in the medaka 5.6-kb proximal element, thus suggesting that the enhancer is not only conserved at sequence level but also functionally in vertebrates. This is in line with what has been observed for a majority of the CNEs comparatively tested in vertebrate species 54 . Here we have identified conserved binding sites for TF Vsx2 in the H6_10137 region, and showed that they are required to direct its regulatory activity to the neural retina domain.…”
Section: Discussionsupporting
confidence: 92%
“…An equivalent region driving the expression to the developing eye is present in the medaka 5.6-kb proximal element, thus suggesting that the enhancer is not only conserved at sequence level but also functionally in vertebrates. This is in line with what has been observed for a majority of the CNEs comparatively tested in vertebrate species 54 . Here we have identified conserved binding sites for TF Vsx2 in the H6_10137 region, and showed that they are required to direct its regulatory activity to the neural retina domain.…”
Section: Discussionsupporting
confidence: 92%
“…al that shows overlapping TFBS within their tested UCEs are more stringently conserved [12]. The same study proposed that heavily overlapping TFBSs could count for the UCEs conservation [12], although this theory has been previously questioned by others [9]. Our study confirmed that UCEs are enriched for TFBSs compared to the same size of random genomic regions (Figure 3).…”
Section: Discussionsupporting
confidence: 78%
“…This supports a model in which UCEs can act in concert as long range enhancers [4], [10], [11], and would explain their juxtaposition to developmental regulators. Further supporting the enhancer function of UCEs are the observations that UCEs can act as developmental enhancers and ‘hubs’ for transcription factor binding sites [4], [9], [10], [12]. However, the reason for their extreme conservation is not evident from this enhancer activity, especially since other enhancers have been described which are functionally strongly conserved without a concomitant conservation in their primary sequence [9].…”
Section: Introductionmentioning
confidence: 99%
“…These features, which can be considered controls, included six that were previously shown to be nonrandomly associated with UCE positions: copy number variants (CNVs), cancer-specific copy number alterations (CNAs), genes, exons, introns, and segmental duplications (SDs) (Chiang et al, 2008; Derti et al, 2006; McCole et al, 2014). They also included open chromatin, since UCEs have been linked to transcriptional activity (reviewed in Baira et al, 2008; Fabris and Calin, 2017; Harmston et al, 2013), repetitive elements, which UCEs avoid (Bejerano et al, 2004; Chiang et al, 2008; Derti et al, 2006; McCole et al, 2014), and GC content, which is associated with the positions of CNVs (Koren et al, 2012). We divided the genome into equally sized bins and, because domains and the nine control features span a vast range of sizes, our analyses involved multiple iterations using a range of bin sizes (20, 50, and 100 kb).…”
Section: Resultsmentioning
confidence: 99%
“…To explore this process of evolutionary ‘‘composition,’’ we are investigating the relationships between chromosome organization and sequence evolution in the mammalian genome, focusing on some of the most highly conserved regions—the ultraconserved elements (UCEs) (Bejerano et al, 2004; Sandelin et al, 2004; Woolfe et al, 2005). UCEs show staggering levels of interspecies sequence conservation, demonstrating perfect sequence identity extending ≥200 bp between species that diverged 90–300 million years ago and comprising one of the most puzzling findings in comparative genomics (Harmston et al, 2013; Polychronopoulos et al, 2017). While UCEs have been found to encompass a variety of functions, including enhancer, promoter, splicing, and repressive activities (Bejerano et al, 2004; Dickel et al, 2018; Kushawah and Mishra, 2017;Pennacchio et al, 2006; Poitras et al, 2010; Sandelin et al, 2004; Warnefors et al, 2016), these functions arguably fall short of explaining ultraconservation, per se.…”
Section: Introductionmentioning
confidence: 99%